Prevalence of Intestinal Parasitic and Bacterial Pathogens in Diarrhoeal and Non-diarroeal Human Stools from Vhembe District, South Africa (Journal of Health, Population and Nutrition, 2010)
In the present study, a cross-sectional survey of intestinal parasitic and bacterial infections in relation to diarrhoea in Vhembe district and the antimicrobial susceptibility profiles of isolated bacterial pathogens was conducted. Stool samples were collected from 528 patients attending major public hospitals and 295 children attending two public primary schools and were analyzed by standard microbiological and parasitological techniques. Entamoeba histolytica/E. dispar (34.2%) and Cryptosporidium spp. (25.5%) were the most common parasitic causes of diarrhoea among the hospital attendees while Giardia lamblia (12.8%) was the most common cause of diarrhoea among the primary school children (p